DOP26 The relationship between vedolizumab therapeutic drug monitoring, biomarkers of inflammation, and clinical outcomes in Inflammatory Bowel Disease in the real-world setting. (27th May 2021) - Afif, W; Marshall, J K; Kaidanovich-Beilin, O; Ward, R; Seow, C
Abstract: Background: Despite widespread use of therapeutic drug monitoring to guide anti-TNF biologic prescribing in IBD, its role for other biologic classes remains unclear. The present study aimed to assess the relationship between early vedolizumab trough concentrations (VTC) and real-world outcomes in inflammatory bowel disease (IBD). Methods: Individuals with IBD enrolled in the Takeda Canada Patient Support Program were assessed at regular intervals from 2018–2020. VTC, albumin, faecal calprotectin (FC), C-reactive protein (CRP), and disease scores were collected from Crohn's disease (CD; Harvey-Bradshaw Index, HBI) and ulcerative colitis (UC; Partial Mayo scores, PMS) patients. The relationship between post-induction (Week 6) VTC, baseline albumin, and Week 30 remission as defined by CRP (<5mg/L), FC (<250µg/g), or disease scores (HBI <5; PMS <3) was assessed. Results: Week 6 VTC levels were higher in IBD patients who achieved Week 30 CRP remission compared with those who did not (n=248, p=0.0004). The Week 6 VTC cut-off that best predicted CRP remission for all IBD patients was 39.65µg/mL (AUROC: 0.61, 95% CI: 0.54–0.69, p<0.001), with significance in both univariate (n=248; p<0.001) and multivariate (p=0.002) analyses. In disease-specific subgroups, optimal VTC cut-offs in CD and UC patients displayed this same relationship. UC patients with Week 6 VTC levels >39.65µg/mL had significantly longer treatment duration (n=115; HR: 0.29, 95% CI: 0.10–0.86); CD patients did not. Week 6 VTC levels were higher in IBD patients who achieved Week 30 FC remission compared with those who did not (n=170, p=0.003). The Week 6 VTC cut-off that best predicted Week 30 FC remission for all IBD patients was 41.9µg/mL (AUROC: 0.62, 95% CI: 0.54–0.7, p<0.0001), with significance in univariate (n=170; p=0.002) but not multivariate analyses. Baseline albumin levels in all IBD patients were independently associated with Week 30 FC remission by multivariate analyses (n=170, p=0.006). In disease-specific subgroups, optimal Week 6 VTC cut-offs and baseline albumin levels were associated with Week 30 FC remission in CD patients only. All IBD patients with Week 6 VTC levels >41.9µg/mL had longer treatment duration (n=170; HR: 0.31, 95% CI: 0.12–0.83). No relationships were found between Week 6 VTC and HBI or PMS disease scores. Conclusion: Post-induction VTC predicts remission by CRP in individuals with CD and UC but not remission by FC or clinical disease indices. Baseline albumin is independently associated with FC remission. Further research is warranted to better understand these relationships, and to develop multivariable predictive tools that combine baseline biomarkers with early vedolizumab pharmacokinetics.